Determination of elastic-plastic and visco-plastic material properties from instrumented indentation curves - Kang, JiJun (2013)
Instrumented indentation techniques at micro or nano-scales have become more popular for determining mechanical properties from small samples of material. These techniques can be used not only to obtain and to interpret the hardness of the material but also to provide information about the near surface mechanical properties and deformation behaviour of bulk solids and/or coating films. In particular, various approaches have been proposed to evaluate the elastic-plastic properties of power-law materials from the experimental loading-unloading curves. In order to obtain a unique set of elastic-plastic properties, many researchers have proposed to use more than one set of loading-unloading curves obtained from different indenter geometries.